2012
DOI: 10.1073/pnas.1210180110
|View full text |Cite
|
Sign up to set email alerts
|

Golden triangle for folding rates of globular proteins

Abstract: The ability of protein chains to spontaneously form their spatial structures is a long-standing puzzle in molecular biology. Experimentally measured rates of spontaneous folding of single-domain globular proteins range from microseconds to hours: the difference (11 orders of magnitude) is akin to the difference between the life span of a mosquito and the age of the universe. Here, we show that physical theory with biological constraints outlines a "golden triangle" limiting the possible range of folding rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
113
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(116 citation statements)
references
References 36 publications
(30 reference statements)
3
113
0
Order By: Relevance
“…For the same database of 65 two-state proteins, the prediction results are listed in Table 6. From Table 6 we find the present prediction is better than other empirical models in the correlation coefficient R and it is comparable with model ACO, SMCO and L eff but better than others in the standard error σ. Garbuzynskiy et al [42] recently proved that the measured protein folding rates fall within a narrow triangle (called Golden triangle). Our results give an explanation for the origin of the Golden triangle.…”
Section: Results Of Statistical Analysis Of 65 Two-state Protein Foldmentioning
confidence: 99%
See 4 more Smart Citations
“…For the same database of 65 two-state proteins, the prediction results are listed in Table 6. From Table 6 we find the present prediction is better than other empirical models in the correlation coefficient R and it is comparable with model ACO, SMCO and L eff but better than others in the standard error σ. Garbuzynskiy et al [42] recently proved that the measured protein folding rates fall within a narrow triangle (called Golden triangle). Our results give an explanation for the origin of the Golden triangle.…”
Section: Results Of Statistical Analysis Of 65 Two-state Protein Foldmentioning
confidence: 99%
“…(i) Study the relationship between folding free energy ∆G and N. At a given temperature, it was reported that the folding free energy ∆G of a polypeptide chain is approximately proportional to chain length [42,56]. Accordingly, we investigated ∆G with N for 65 two-state proteins and found a good linear relationship existing in these two quantities:…”
Section: Statistical Investigations On the Folding Rates Of 65 Two-stmentioning
confidence: 99%
See 3 more Smart Citations